Քաղաքական ազդեցության հիմնահարցը Անտիոքի իշխանության և Կիլիկյան Հայաստանի փոխհարաբերություններում - Ավետիսյան, Վահե
As a result of the First Crusade in the Middle East, four Latin states were formed. Of these, the Principality of Antioch from the very beginning of its existence laid claim to Cilicia which then belonged to the Byzantine Empire. With the strengthening of the Cilician Armenian state and the gradual weakening of the Empire, the question as to the ownership of these territories arose. Since Antioch lacked necessary forces for direct control over the disputed territories, the only possible way to achieve the desired goal was to make an attempt of political influence on the Armenian Court. However, from a certain moment the Armenian nobility itself resorted to this method of influence on the Principality of Antioch. В результате первого крестового похода на Ближнем Востоке образовались четыре латинских государства. Из них Антиохийское княжество уже с самого начала своего существования претендовало на Киликию, принадлежащую тогда Византии. В условиях усиления Киликийского армянского государства и постепенного ослабления Византийской империи, встал вопрос о принадлежности этих территорий. Отсутствие у Антиохийского княжества необходимых для прямого контроля над спорными территориями сил, сделало попытки политического влияния на армянский двор единственным возможным способом достижения желаемого. Однако с определенного момента сама армянская знать прибегла к этому методу для воздействия на Антиохийское княжество.
Keywords: Պատմություն